A Tb 3+ Method for preparing doped organic-inorganic three-dimensional double perovskite and applications
Patent Information
- Application Number
- CN202410207019.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-26
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-02-26
AI Technical Summary
但必须设计合理的反应路线和选择合适的反应条件
[0019]1.本发明利用恒温蒸发法制备的Tb3+掺杂有机-无机杂化双钙钛矿,相比于商业荧光粉,本发明采用的方法具有条件温和与工艺流程简单等优点,同时单晶材料具有的红光发射量子产率为75.76%,绿光发射量子产率为87.08%,荧光寿命大于4ms,具有较好的荧光性能。
Smart Images

Figure CN118221531B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chemical material preparation technology, and particularly relates to a Tb 3+ Preparation methods and applications of doped organic-inorganic three-dimensional double perovskites. Background Technology
[0002] Luminescent materials with high photoluminescence quantum yields (PLQYs) can effectively improve lighting efficiency and reduce energy waste. A commonly used commercial red fluoride is K₂SiF₆:Mn. 4+ and K2TiF6:Mn 4+ The quantum yield is low, between 40% and 50%. Commercially available green phosphors are primarily aluminates (Y3Al5O3). 12 :Ce 3+ Their quantum yields range from 60% to 70%. These green and red phosphors not only have low quantum yields, but their synthesis processes are also relatively complex and expensive, thus limiting their market application. Hybrid perovskite materials exhibit ultra-high light absorption coefficients and ultra-low volume defect densities, demonstrating significant advantages in high luminous efficiency.
[0003] Three-dimensional rare earth-based hybrid double perovskite A2M + M 3+(NO3)6 has become a research hotspot due to its low synthesis cost, environmental friendliness, high stability, and low energy barrier. Meanwhile, the rare-earth ions in three-dimensional rare-earth-based hybrid double perovskite exhibit more stable intrinsic photoluminescence properties and are less susceptible to quenching by excessive luminescent activators, potentially leading to higher light emission efficiency. However, there is a lack of research reports on yellow phosphors, which play a crucial role in improving the efficiency and color rendering index of commercial white LEDs. Therefore, developing environmentally friendly and efficient novel three-dimensional hybrid double perovskite yellow phosphors is of significant practical importance for promoting the application of high color rendering index white LED technology. In the [(CH3)4N)]2KLn(NO3)6 system, the highly symmetric A-site cation can reduce the localization of partial charge density, thereby increasing the quantum yield. To date, existing techniques are limited to exploring the photoluminescence phenomenon of [(CH3)4N)]2KEu(NO3)6 under 532nm excitation; no reports have been found on studying the optical properties of this compound from the perspectives of structural regulation (doping) and changing the excitation wavelength. Single-crystal materials exhibit greater order and completeness in their crystal structure, with fewer optical defects (such as absorption centers and excited-state dissipation). High-quality single crystals contribute to improved fluorescence performance and luminescence efficiency. Currently used synthesis methods, such as hydrothermal methods, additive methods, seed growth methods, and reverse-temperature crystallization methods, all demonstrate a certain degree of complexity in their synthesis processes. Compared to other single-crystal growth techniques, the slow solvent evaporation method is easier to implement, requiring relatively simple equipment and technology. However, it necessitates the design of a reasonable reaction route and the selection of appropriate reaction conditions. Therefore, we propose a Tb... 3+ Preparation methods and applications of doped organic-inorganic three-dimensional double perovskites. Summary of the Invention
[0004] The purpose of this invention is to provide a Tb 3+ The preparation method and application of +doped organic-inorganic three-dimensional double perovskite are intended to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A type of Tb 3+ Doped with organic-inorganic three-dimensional double perovskite, the chemical formula of the double perovskite luminescent material is [(CH3)4N)]2KEu 1-x Tb x (NO3)6, of which Tb 3+ The doping amount is 0 <x≤1。
[0007] —Furthermore, the dual perovskite luminescent material is a single crystal, and the single crystal structure belongs to the cubic crystal system, space group Fm3m; Tb 3+ The doping is specifically Tb 3+ Ions occupy Eu3+ Doping is performed at specific locations; the minimum single crystal size is 3×2×2mm. 3 The single crystal has a red light emission quantum yield of 75.76% and a green light emission quantum yield of 87.08%.
[0008] Furthermore, with the aforementioned Tb 3+ As the doping amount x increases, the emission spectrum of the single crystal gradually changes from red light to orange light, yellow light, and finally green light.
[0009] Furthermore, when the value of x is 0.55≤x≤0.7, the double perovskite luminescent material is used as a yellow phosphor or applied to white LEDs, with a color rendering index Ra greater than 90.
[0010] A Tb as described above 3+ A method for preparing doped organic-inorganic three-dimensional double perovskite includes the following steps:
[0011] Step A: Mix tetramethylammonium salt, potassium source, europium source and terbium source in a certain proportion;
[0012] Step B: Place the mixture from Step A into a glass bottle, add a certain amount of deionized water, and stir.
[0013] Step C: Place the glass bottle containing the mixed solution from Step B with the lid off in an oven and evaporate it at a constant temperature for a period of time until the single crystal growth is complete.
[0014] Step D: Rinse the single crystal obtained in step C thoroughly with n-hexane, and then dry it in an oven at 70°C.
[0015] Furthermore, in step A, the molar ratio of tetramethylammonium salt, potassium source, europium source and terbium source satisfies 2:1:(1-y):y, where the value of y is 0≤y≤1.
[0016] Furthermore, in step B, the volume of deionized water is 10–30 mL.
[0017] Furthermore, in step C, the evaporation temperature is 40–70°C, and the evaporation time is 3–5 days.
[0018] Compared with the prior art, the beneficial effects of the present invention are:
[0019] 1. This invention utilizes a constant-temperature evaporation method to prepare Tb 3+ Compared to commercial phosphors, the method used in this invention for doping organic-inorganic hybrid perovskites has advantages such as milder conditions and simpler process flow. At the same time, the single crystal material has a red light emission quantum yield of 75.76%, a green light emission quantum yield of 87.08%, and a fluorescence lifetime of more than 4ms, exhibiting good fluorescence performance.
[0020] 2. This invention synthesizes a novel three-dimensional double perovskite luminescent material that emits yellow light. It has high thermal stability and can remain stable at 365℃. It can be used to assemble white LEDs with a color rendering index greater than 90, and has good application prospects in the lighting field. Attached Figure Description
[0021] Figure 1 In the figure, (a) is the XRD pattern obtained by simulation analysis of single crystal diffraction data of samples in Examples 1 to 7; (b) is the (022) diffraction peak of samples in Examples 1 to 7.
[0022] Figure 2 These are thermogravimetric spectra of the samples in Examples 1 to 7 of the present invention.
[0023] Figure 3 In the figure, (a) is the fluorescence performance of the sample in Example 1 under 592nm excitation; (b) is the fluorescence performance of the sample in Example 1 under 397nm excitation; (c) is the fluorescence lifetime decay curve of the single crystal sample in Example 1 under 397nm excitation monitoring at 592nm emission; and (d) is the fluorescence quantum yield test graph of the single crystal sample in Example 1 under 397nm excitation.
[0024] Figure 4 In the figure, (a) is the fluorescence performance of the sample in Example 7 under 545nm excitation; (b) is the fluorescence performance of the sample in Example 7 under 380nm excitation; (c) is the fluorescence lifetime decay curve of the single crystal sample in Example 7 under 380nm excitation monitoring at 545nm emission; and (d) is the fluorescence quantum yield test graph of the single crystal sample in Example 7 under 380nm excitation.
[0025] Figure 5 In the figure, (a) shows the fluorescence performance of the samples in Examples 1 to 7 under 365 nm excitation; (b) shows the CIE color coordinates of the powder samples in Examples 1 to 7 under 365 nm excitation.
[0026] Figure 6 In the diagram, (a) shows the performance of the LED prepared by mixing the sample with commercial blue phosphor in Example 6 and using a 365nm chip; (b) shows the color coordinates of the LED prepared by mixing the sample with commercial blue phosphor in Example 6 and using a 365nm chip. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0028] The specific implementation of the present invention will be described in detail below with reference to specific embodiments.
[0029] An embodiment of the present invention provides a Tb 3+ Doped with organic-inorganic three-dimensional double perovskite, the chemical formula of the double perovskite luminescent material is [(CH3)4N)]2KEu 1-x Tb x (NO3)6, of which Tb 3+ The doping amount is 0 <x≤1。
[0030] In a preferred embodiment of the present invention, the dual perovskite luminescent material is a single crystal, and the single crystal junction...
[0031] —It belongs to the cubic crystal system, space group Fm3m; Tb 3+ The doping is specifically Tb 3+ Ions occupy Eu 3+ Doping is performed at specific locations; the minimum single crystal size is 3×2×2mm. 3 The single crystal has a red light emission quantum yield of 75.76% and a green light emission quantum yield of 87.08%.
[0032] As a preferred embodiment of the present invention, with the Tb 3+ As the doping amount x increases, the emission spectrum of the single crystal gradually changes from red light to orange light, yellow light, and finally green light.
[0033] In a preferred embodiment of the present invention, when the value of x is 0.55≤x≤0.7, the double perovskite luminescent material is used as a yellow phosphor or applied to white LEDs, and the color rendering index Ra is greater than 90.
[0034] One embodiment of the present invention provides a Tb as described above. 3+ A method for preparing doped organic-inorganic three-dimensional double perovskite includes the following steps:
[0035] Step A: Mix tetramethylammonium salt, potassium source, europium source and terbium source in a certain proportion; the molar ratio of tetramethylammonium salt, potassium source, europium source and terbium source shall satisfy 2:1:(1-y):y, and the value of y is 0≤y≤1;
[0036] Step B: Place the mixture from Step A into a glass bottle, add 10-30 mL of deionized water, and stir thoroughly.
[0037] Step C: Place the glass bottle containing the mixed solution from Step B with the cap open in an oven and evaporate at a constant temperature of 40-70°C for 3-5 days until the single crystal growth is complete.
[0038] Step D: Rinse the single crystal obtained in step C thoroughly with n-hexane, and then dry it in an oven at 70°C.
[0039] Example 1: Preparation of sample #1;
[0040] Weigh out 10 mmol of tetramethylammonium salt, 5 mmol of potassium salt, and 5 mmol of europium salt, mix them in a glass bottle, add 10 ml of deionized water, and stir thoroughly for a period of time to prepare a solution of a certain concentration. Then, place the bottle open in an oven and evaporate at a constant temperature of 50°C until the single crystal growth is complete. The resulting single crystal is thoroughly rinsed with n-hexane and dried in an oven at 70°C to obtain Tb. 3+ For a sample with zero doping, the resulting single crystals can be ground to obtain the corresponding powder sample.
[0041] Example 2: Preparation of sample #2;
[0042] Weigh out 10 mmol of tetramethylammonium salt, 5 mmol of potassium salt, 2.5 mmol of europium salt, and 2.5 mmol of terbium salt, mix them in a glass bottle, add 10 ml of deionized water, and stir thoroughly for a period of time to prepare a solution of a certain concentration. Then, place the bottle open in an oven and evaporate at a constant temperature of 50°C until the single crystal growth is complete. The resulting single crystal is rinsed with n-hexane and dried in an oven at 70°C to obtain Tb. 3+ The sample with a doping amount of 0.15 can be ground to obtain the corresponding powder sample.
[0043] Example 3: Preparation of sample #3;
[0044] Weigh out 10 mmol of tetramethylammonium salt, 5 mmol of potassium salt, 2 mmol of europium salt, and 3 mmol of terbium salt, mix them in a glass bottle, add 10 ml of deionized water, and stir thoroughly for a period of time to prepare a solution of a certain concentration. Then, place the bottle open in an oven and evaporate at a constant temperature of 50°C until the single crystal growth is complete. The resulting single crystal is rinsed with n-hexane and dried in an oven at 70°C to obtain Tb. 3+ The sample with a doping amount of 0.19 can be ground to obtain the corresponding powder sample.
[0045] Example 4: Preparation of sample #4;
[0046] Weigh out 10 mmol of tetramethylammonium salt, 5 mmol of potassium salt, 1.5 mmol of europium salt, and 3.5 mmol of terbium salt, mix them in a glass bottle, add 10 ml of deionized water, and stir thoroughly for a period of time to prepare a solution of a certain concentration. Then, place the bottle open in an oven and evaporate at a constant temperature of 50°C until the single crystal growth is complete. The resulting single crystal is rinsed with n-hexane and dried in an oven at 70°C to obtain Tb. 3+ The sample with a doping level of 0.29 can be ground to obtain the corresponding powder sample.
[0047] Example 5: Preparation of sample #5;
[0048] Weigh out 10 mmol of tetramethylammonium salt, 5 mmol of potassium salt, 1 mmol of europium salt, and 4 mmol of terbium salt, mix them in a glass bottle, add 10 ml of deionized water, and stir thoroughly for a period of time to prepare a solution of a certain concentration. Then, place the bottle open in an oven and evaporate at a constant temperature of 50°C until the single crystal growth is complete. The resulting single crystal is rinsed with n-hexane and dried in an oven at 70°C to obtain Tb. 3+ The sample with a doping amount of 0.44 can be ground to obtain the corresponding powder sample.
[0049] Example 6: Preparation of sample #6;
[0050] Weigh out 10 mmol of tetramethylammonium salt, 5 mmol of potassium salt, 0.5 mmol of europium salt, and 4.5 mmol of terbium salt, mix them in a glass bottle, add 10 ml of deionized water, and stir thoroughly for a period of time to prepare a solution of a certain concentration. Then, place the bottle open in an oven and evaporate at a constant temperature of 50°C until the single crystal growth is complete. The resulting single crystal is rinsed with n-hexane and dried in an oven at 70°C to obtain Tb. 3+ The sample with a doping amount of 0.62 can be ground to obtain the corresponding powder sample.
[0051] Example 7: Preparation of sample #7;
[0052] Weigh out 10 mmol of tetramethylammonium salt, 5 mmol of potassium salt, and 5 mmol of terbium salt, mix them in a glass bottle, add 10 ml of deionized water, and stir thoroughly for a period of time to prepare a solution of a certain concentration. Then, place the bottle open in an oven and evaporate at a constant temperature of 50°C until the single crystal growth is complete. The resulting single crystal is rinsed with n-hexane and dried in an oven at 70°C to obtain Tb. 3+ For a sample with a doping level of 1, the resulting single crystals can be ground to obtain the corresponding powder sample.
[0053] Phase composition and thermal stability analysis of Comparative Example 8 and Samples #1 to #7;
[0054] The single-crystal XRD diffraction simulation patterns of the synthesized samples in Examples 1-7 are shown below. Figure 1 As shown, the diffraction peaks of samples #2 to #7 match those of sample #1, confirming that all samples are pure phases. Furthermore, with Tb... 3+ As the doping concentration x increases, the (022) diffraction peak shifts to a higher angle. The cell parameters of samples #1 to #7 were specifically obtained through analysis. Unit cell volume Cell volume V and the amount of Tb incorporated 3+ The linear relationship between the quantity x is: Thermogravimetric analysis spectra of samples #1 to #7 are as follows Figure 2 As shown, samples #1 to #7 have good thermal stability before 365℃, and begin to thermally decompose only after 365℃. Furthermore, the samples have good overlap.
[0055] Fluorescence performance tests of Comparative Example 9, single crystal samples #1 and #7;
[0056] The fluorescence performance test results of single crystal sample #1 are shown in the figure below. Figure 3 As shown, red light emission is observed under 397 nm excitation. The calculated quantum yield of the single crystal is 75.76%, and the fitted fluorescence lifetime of the single crystal is 4.8 ms. The fluorescence performance test results for single crystal sample #7 are shown below. Figure 4 As shown, green light emission is observed under 380nm excitation. The calculated quantum yield of the single crystal is 87.08%, and the fitted fluorescence lifetime is 8.22ms. It is evident that single crystal samples #1 and #7 exhibit high quantum yields in both red and green light emission, which holds promise for improving energy efficiency and has potential applications in the display and lighting fields.
[0057] Comparative Example 10: Fluorescence performance test of powder samples #1 to #7 under 365nm excitation;
[0058] The fluorescence performance test results of powder samples #1-#7 under 365nm excitation are shown in the figure below. Figure 5 As shown, powder samples #1-#7 exhibit tunable emission, gradually changing from red to orange, then to yellow, and finally to green. Powder sample #6 emits yellow light when excited at 365nm.
[0059] Comparative Example 11: Fabrication of white LED based on Sample #6;
[0060] Sample #6, a mixture of yellow phosphor and commercially available blue phosphor, was coated onto a commercial 365nm ultraviolet chip to fabricate a white LED. Figure 6 As shown, the manufactured white LED emits white light under a 30mA driving power supply, with CIE color coordinates of (0.30, 0.32), a correlated color temperature (CCT) of 7600K, and a color rendering index (Ra) of 90.3. It is expected to have practical applications in the manufacture of light-emitting devices and phosphors.
[0061] The above are merely preferred embodiments of the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent.
Claims
1. A kind Doped organic-inorganic three-dimensional double perovskite, characterized in that, The chemical formula of the double perovskite luminescent material is: ,in, The doping amount is 0 <x≤1。 2. As described in claim 1 Doped organic-inorganic three-dimensional double perovskite, characterized in that, The dual perovskite luminescent material is a single crystal, and the single crystal structure belongs to the cubic crystal system. Space group; Doping specifically refers to Ion Occupation Doping is performed at specific locations; the minimum single crystal size is [missing information]. The single crystal has a red light emission quantum yield of 75.76% and a green light emission quantum yield of 87.08%.
3. As described in claim 2 Doped organic-inorganic three-dimensional double perovskite, characterized in that, With the Tb 3+ As the doping amount x increases, the emission spectrum of the single crystal gradually changes from red light to orange light, yellow light, and finally green light.
4. As described in claim 2 Doped organic-inorganic three-dimensional double perovskite, characterized in that, When the value of x is 0.55≤x≤0.7, the double perovskite luminescent material is used as a yellow phosphor or applied to white LEDs, with a color rendering index Ra greater than 90.
5. A device according to any one of claims 1-4 A method for preparing doped organic-inorganic three-dimensional double perovskite, characterized in that, Includes the following steps: Step A: Mix tetramethylammonium salt, potassium source, europium source and terbium source in a certain proportion; Step B: Place the mixture from Step A into a glass bottle, add a certain amount of deionized water, and stir. Step C: Place the glass bottle containing the mixed solution from Step B with the lid off in an oven and evaporate it at a constant temperature for a period of time until the single crystal growth is complete. Step D: Rinse the single crystal obtained in step C thoroughly with n-hexane, and then dry it in an oven at 70°C.
6. The method according to claim 5 A method for preparing doped organic-inorganic three-dimensional double perovskite, characterized in that, In step A, the molar ratio of tetramethylammonium salt, potassium source, europium source, and terbium source satisfies 2:1:(1-y):y, where the value of y is 0. <y≤1。 7. The method according to claim 5 A method for preparing doped organic-inorganic three-dimensional double perovskite, characterized in that, In step B, the volume of deionized water is 10-30 mL.
8. The method according to claim 5 A method for preparing doped organic-inorganic three-dimensional double perovskite, characterized in that, In step C, the evaporation temperature is 40~70℃ and the evaporation time is 3~5 days.